Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1074/jbc.274.21.15237
|View full text |Cite
|
Sign up to set email alerts
|

p53 Suppresses the Activation of the Bcl-2 Promoter by the Brn-3a POU Family Transcription Factor

Abstract: The Brn-3a POU family transcription factor has been shown to strongly activate expression of the Bcl-2 protooncogene and thereby protect neuronal cells from programmed cell death (apoptosis). This activation of the Bcl-2 promoter by Brn-3a is strongly inhibited by the p53 anti-oncogene protein. This inhibitory effect of p53 on Brn-3a-mediated transactivation is observed with nonoverlapping gene fragments containing either the Bcl-2 p1 or p2 promoters but is not observed with other Brn-3a-activated promoters su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
129
1
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(133 citation statements)
references
References 34 publications
1
129
1
2
Order By: Relevance
“…21 Homeobox/POU domain protein 3A (BRN-3A) (AA428196) is expressed at 124 h. This protein was previously shown to be expressed in activated Jurkat T cells 22 where it activates Bcl-2 proto-oncogene expression, thereby protecting cells from apoptosis. 23 IRX-2a (R46202), which participates in epithelial cell differentiation, 24 is expressed late in the time course.…”
Section: --------------------------------------------------------------mentioning
confidence: 99%
“…21 Homeobox/POU domain protein 3A (BRN-3A) (AA428196) is expressed at 124 h. This protein was previously shown to be expressed in activated Jurkat T cells 22 where it activates Bcl-2 proto-oncogene expression, thereby protecting cells from apoptosis. 23 IRX-2a (R46202), which participates in epithelial cell differentiation, 24 is expressed late in the time course.…”
Section: --------------------------------------------------------------mentioning
confidence: 99%
“…This dual regulation allows an accelerated transition to the offstate. This may be the case for Bcl-2, because its transcription is directly repressed by p53, as discussed above, 14 and its 3 0 -UTR is targeted by miR-34a. 35 …”
Section: Btg4mentioning
confidence: 99%
“…13 For example, the survival factor, Bcl-2, is transcriptionally repressed by p53 through steric interference with DNA binding of the POU4F1 transcription factor at the Bcl-2 promoter. 14 The discovery of microRNAs (miRNAs) suggested that the p53-mediated induction of miRNAs might contribute to the downregulation of proteins observed after p53 activation. miRNAs form a class of endogenously expressed, small noncoding RNAs that mediate post-transcriptional regulation of gene expression (reviewed in Ref.…”
mentioning
confidence: 99%
“…The ND7 cell line, which is derived by fusing non-dividing rat dorsal root ganglion cells with the C1300 mouse neuroblastoma cell line was previously described, 22 and the p53 null human osteogenic sarcoma cell line SAOS-2 cell line was obtained from ATCC (USA). For culture, ND7 cells were grown in full growth media (1 Â L15 with 10% fetal calf serum (FCS)) supplemented with 0.3% glucose, 0.37% sodium bicarbonate and 0.2 mM L-glutamine.…”
Section: Methodsmentioning
confidence: 99%
“…For example, ASPP1/2 proteins interact with p53 and TAp73 proteins to enhance transcription of pro-apoptotic genes 19 whereas Brn-3a interacts with p53 but differentially regulates its ability to transactivate its target genes. [20][21][22] p73 KO mice display varying degrees of abnormal neurological development in different parts of the nervous system, which results in an increased death rate within weeks after birth. 23 This phenotype seems to be mainly related to the absence of DNp73, thus demonstrating specific functions for p73 isoforms in specific neuronal cells.…”
mentioning
confidence: 99%